ANALISIS PERILAKU KEAGAMAAN REMAJA (STUDI KASUS DI KELURAHAN 2 ULU KOTA PALEMBANG) - Kurnia Oktaria; Fajri Ismail; Muhammad Win Afgani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This paper aims to determine the religious behavior of adolescents in the 2 ulu sub-district of Palembang city. This paper uses the research method in this study is a qualitative method and this type of research includes the type of case study research where case study research is research conducted on a "system unit", this unit can be in the form of programs, activities, events, or a group of individuals who bound by a certain place, time or bond. Case study is a research that is directed to collect data to take meaning, gain understanding from the case. From the results of the study it is known that adolescents who live in the hall of work have very low adherence to religion in the form of religious rituals/practices. This can be seen from the lack of religious activity that they do. However, some of the religious practices of street children that can be observed are praying with a very rare intensity, fasting during the month of Ramadan, and participating in activities on Islamic holidays. Forms of behavior and religious values that live among adolescents as a consequence of religion, are applied in social life in the form of solidarity between friends, helping each other, being polite to older people, working together, being honest, and so on. This behavior they do is a form of worship that they consider important in life.